1990
DOI: 10.3109/08910609009140125
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for the Detection and Enumeration of Xylitol-resistant (fructose-PTS) Strains ofStreptococcus mutansfrom Pure Cultures and Human Saliva

Abstract: A simple procedure for the identification and enumeration, in large bacterial populations, of Streptococcus mutans of both xylitol-resistant and xylitol-sensitive phenotypes was developed. Since xylitol-resistant cells have lost the capacity to take up xylitol from the extracellular medium, due to a defect in their fructose-PTS, there is no uptake of [14C]xylitol by these cells whereas the [14C]xylitol taken up by the sensitive cells is used to visualise them by autoradiography. The method was shown to be suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…On the contrary, natural selection and emergence of mutans streptococci that are resistant to xylitol seem to take place (25, 27). Several studies have shown that emergence of X‐R mutans streptococci occurs rapidly (8), and that the ratio X‐R/X‐S is increased in habitual xylitol consumers (27). Xylitol has no growth‐inhibiting effect on X‐R strains, as also confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, natural selection and emergence of mutans streptococci that are resistant to xylitol seem to take place (25, 27). Several studies have shown that emergence of X‐R mutans streptococci occurs rapidly (8), and that the ratio X‐R/X‐S is increased in habitual xylitol consumers (27). Xylitol has no growth‐inhibiting effect on X‐R strains, as also confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the modest reduction in mutans streptococci is due to the 'fasting' effect of xylitol on oral microorganisms. The adaptation of S.mutans to xylitol has been recognised [73][74][75][76][77] , although the effect of xylitol-insensitive strains of S.mutans on fermentable carbohydrates and on glucan synthesis from sucrose has not been clarified.…”
Section: Xylitolmentioning
confidence: 99%
“…The autoradiography method described by D réan & T rahan (20) formed the base for this analysis. A sterile cellulose nitrate filter (0.45 µm; Sartorius, Bie & Berntsen, Rødovre, Denmark) was placed on a modified MSB agar containing 30% sucrose.…”
Section: Quantification Of Xs Msmentioning
confidence: 99%